Intercellular communication in the brain through a dendritic nanotubular network - Chang, Minhyeok; Krüssel, Sarah; Parajuli, Laxmi Kumar; Kim, Juhyun; Lee, Daniel; Merodio, Alec; Kwon, Jaeyoung; Okabe, Shigeo; Kwon, Hyung-Bae (Science, 2025)
Intercellular nanotubular networks mediate material exchange, but their existence in neurons remains to be explored in detail. We identified long, thin dendritic filopodia forming direct dendrite-dendrite nanotubes (DNTs) in mammalian cortex. Super-resolution microscopy in dissociated neurons revealed DNTs’ actin-rich composition and dynamics, enabling long-range calcium ion (Ca2+) propagation. Imaging and machine learning-based analysis validated in situ DNTs as anatomically distinct from synaptic spines. DNTs actively transported small molecules and human amyloid-β (Aβ); DNT density increased before plaque formation in the medial prefrontal cortex of APP/PS1 mice (APP, Aβ precursor protein; PS1, presenilin-1), suggesting that the dendrite-DNT network might play a role in Alzheimer’s disease pathology. Computational models of DNT-mediated Aβ propagation recapitulated early amyloidosis, predicting selective intracellular accumulation. These findings uncover a nanotubular connectivity layer in the brain, extending neuronal communication beyond classical synapses.